THE EFFECT OF GIVING REWARDS ON EMPLOYEE WORK MOTIVATION AT THE CENTRAL STATISTICS AGENCY OF BONE BOLANGO REGENCY - Sutiyan Hunawa; Titin Dunggio; Ghoriqna Fibahril Wahdah (LP2M Universitas Bina Mandiri Gorontalo, 2024)
The study aims to determine the effect of giving rewards on employee work motivation at the central Statistics Agency of Bone Bolango Regency. This research data was obtained from research questionnaires, observation and literature studies related to research objectives. This research uses quantitative methods. The analysis technique uses simple linier regression analysis using the SPSS application. The total sample was 30 respondents using saturated sampling techniques. The calculation results obtained a calculated t value 0f 4.324 with a significance level of 0.000 which is smaller than 0.05. the regression coefficient of 0.633 states tha every additional 1 reward will is 1, it is predicted tha work motivation will decrease by 0.633. the research results show tha the reward variable has a significant effect on employee work motivation at the Central Statistics Agency (BPS) of Bone Bolango Regency.